SAFETY AND SECURITY IMPROVEMENT IN PUBLIC TRANSPORTATION BASED ON PUBLIC PERCEPTION IN DEVELOPING COUNTRIES - Tri Basuki JOEWONO (IATSS Research, 2006)
Public transportation poses a higher risk of safety and security since there happen to be more passengers in one car. The problem becomes worse in developing countries, because of the lack of suitable and integrated approaches. The aim of this research is to explore the perception of safety and security problems on the part of those parties involved in the operation of public transportation. This perception is used as a base to develop an improvement agenda for the particular context of developing countries. The research employs a questionnaire survey to collect the perception data. This paper explains the perception of users and drivers of paratransit as well as that of non-users and civil servants, concerning safety and security of paratransit in the city of Bandung, Indonesia. The rank of importance for each factor is analyzed by applying the factor analysis. Analysis shows that the user is the most important party involved. The understanding and awareness of the user (including the driver) is the most important variable to improve the condition. Three aspects of an improvement agenda are proposed based on the perception data, namely technology, management, and institution. This agenda is clarified by a set of action plans incorporating the responsible parties and a time frame. The action plan is divided into three terms to define a clear goal for each step. The short-term action focuses on the hardware and on preparing further steps, whereas the medium-term action focuses on developing and improving the standard of safety and security. The long-term action focuses on advancing safety and security practices. The effectiveness of this agenda and action plan rests upon a set of assumptions, such as the degree of seriousness from the authoritative institution, fair distribution of information, the availability of reasonable resources, and coordinated and collaborative action from all parties involved to reach the objective.